2014
DOI: 10.1155/2014/569087
|View full text |Cite
|
Sign up to set email alerts
|

Carum copticumL.: A Herbal Medicine with Various Pharmacological Effects

Abstract: Carum copticum L. commonly known as “Ajwain” is cultivated in many regions of the world including Iran and India, states of Gujarat and Rajasthan. Traditionally, C. copticum has been used in the past for various therapeutic effects including bloating, fatigue, diarrhea, abdominal tumors, abdominal pain, respiratory distress, and loss of appetite. It has other health benefits such as antifungal, antioxidant, antibacterial, antiparasitic, and hypolipidemic effects. This plant contains different important compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 58 publications
2
43
0
1
Order By: Relevance
“…28, 201.97, 194.91 and 38.49 mg/g oil respectively whereas the other nineteen compounds had quantity < 10 mg/g oil. The presence of the three compounds; -terpinene, thymol and P-cymene with high quantity are in good agreement with previous reports on phytochemical investigation of essential oil of this plant 10,14,18,19 . In this study, -pinene had relatively high amount and this was not reported before.…”
Section: Chemical Composition Of Essential Oil and Nhexane Extractsupporting
confidence: 91%
“…28, 201.97, 194.91 and 38.49 mg/g oil respectively whereas the other nineteen compounds had quantity < 10 mg/g oil. The presence of the three compounds; -terpinene, thymol and P-cymene with high quantity are in good agreement with previous reports on phytochemical investigation of essential oil of this plant 10,14,18,19 . In this study, -pinene had relatively high amount and this was not reported before.…”
Section: Chemical Composition Of Essential Oil and Nhexane Extractsupporting
confidence: 91%
“…The results indicated a potent relaxant effect of carvacrol on the tracheal smooth muscles of guinea pigs (Boskabady and Jandaghi, 2003). Moreover, the relaxant effect of C. copticum was reported in a recent review article (Boskabady et al, 2014).…”
Section: Capparis Spinosamentioning
confidence: 73%
“…16) Essential oils containing carvacrol have been widely used in various traditional medicines. 17) Carvacrol possesses anti-inflammatory, antioxidant, and bactericidal properties.…”
mentioning
confidence: 99%